Efficient message transport interface between agent framework and event service. (27th November 2006) - Park, Sang Yong; Han, Seungwok; Youn, Hee Yong
Multi-agent techniques have been continuously evolving as ubiquitous and pervasive computing emerges as a key post-internet paradigm. In the ubiquitous environment, the applications need to exchange the requests asynchronously using an event-based model. While interoperability between the agent platform and event service platform is important for the applications, it has not received much attention yet. In this paper, we propose the Message Transport Interface (MTI), which allows communication between the JADE platform and CORBA-based platform supporting event service. We also develop a new information bus adapter for augmenting the omniEvent service, which is used for autonomic administration of the channels. The developed system has been implemented in both C++ and Java for Linux and Windows platform, including the pocket PC adapter for mobile computing. Experimental results reveal that the proposed schemes allow much smaller process time than the existing omniEvent service. They are parts of a ubiquitous computing middleware called Component-based Autonomic Layered Middleware (CALM), which is currently under development.